Bio-Catalytic Structural Transformation of Anti-cancer Steroid, Drostanolone Enanthate with Cephalosporium aphidicola and Fusarium lini, and Cytotoxic Potential Evaluation of Its Metabolites against Certain Cancer Cell Lines - Choudhary, M. Iqbal; Siddiqui, Mahwish; Atia-tul-Wahab,; Yousuf, Sammer; Fatima, Narjis; Ahmad, Malik S.; Choudhry, Hani (Frontiers in Pharmacology, 2017)
In search of selective and effective anti-cancer agents, eight metabolites of anti-cancer steroid, drostanolone enanthate (1), were synthesized via microbial biotransformation. Enzymes such as reductase, oxidase, dehydrogenase, and hydrolase from Cephalosporium aphidicola, and Fusarium lini were likely involved in the biotransformation of 1 into new metabolites at pH 7.0 and 26°C, yielding five new metabolites, 2α-methyl-3α,14α,17β-trihydroxy-5α-androstane (2), 2α-methyl-7α-hydroxy-5α-androstan-3,17-dione (3), 2-methylandrosta-11α-hydroxy-1, 4-diene-3,17-dione (6), 2-methylandrosta-14α-hydroxy-1,4-diene-3,17-dione (7), and 2-methyl-5α-androsta-7α-hydroxy-1-ene-3,17-dione (8), along with three known metabolites, 2α-methyl-3α,17β-dihydroxy-5α-androstane (4), 2-methylandrosta-1, 4-diene-3,17-dione (5), and 2α-methyl-5α-androsta-17β-hydroxy-3-one (9), on the basis of NMR, and HREI-MS data, and single-crystal X-ray diffraction techniques. Interestingly, C. aphidicola and F. lini were able to catalyze hydroxylation only at alpha positions of 1. Compounds 1–9 showed a varying degree of cytotoxicity against HeLa (human cervical carcinoma), PC3 (human prostate carcinoma), H460 (human lung cancer), and HCT116 (human colon cancer) cancer cell lines. Interestingly, metabolites 4 (IC50 = 49.5 ± 2.2 μM), 5 (IC50 = 39.8 ± 1.5 μM), 6 (IC50 = 40.7 ± 0.9 μM), 7 (IC50 = 43.9 ± 2.4 μM), 8 (IC50 = 19.6 ± 1.4 μM), and 9 (IC50 = 25.1 ± 1.6 μM) were found to be more active against HeLa cancer cell line than the substrate 1 (IC50 = 54.7 ± 1.6 μM). Similarly, metabolites 2 (IC50 = 84.6 ± 6.4 μM), 3 (IC50 = 68.1 ± 1.2 μM), 4 (IC50 = 60.4 ± 0.9 μM), 5 (IC50 = 84.0 ± 3.1 μM), 6 (IC50 = 58.4 ± 1.6 μM), 7 (IC50 = 59.1 ± 2.6 μM), 8 (IC50 = 51.8 ± 3.4 μM), and 9 (IC50 = 57.8 ± 3.2 μM) were identified as more active against PC-3 cancer cell line than the substrate 1 (IC50 = 96.2 ± 3.0 μM). Metabolite 9 (IC50 = 2.8 ± 0.2 μM) also showed potent anticancer activity against HCT116 cancer cell line than the substrate 1 (IC50 = 3.1 ± 3.2 μM). In addition, compounds 1–7 showed no cytotoxicity against 3T3 normal cell line, while compounds 8 (IC50 = 74.6 ± 3.7 μM), and 9 (IC50 = 62.1 ± 1.2 μM) were found to be weakly cytotoxic.